Analysis of socio‐economic spending and human capital development nexus in Nigeria. Issue 243 (12th September 2021) - Madueme, Stella. I.; Orji, Anthony; Johnson, Idongesit Friday; Anthony‐Orji, Onyinye I.
Abstract: This study examines the impact of Economic and Social Sector Expenditures on Human Capital Development in Nigeria from 1981 to 2018. The Autoregressive Distributive Lag Model was applied in the analysis. The results reveal that the lagged values of government economic expenditure, student – teachefr ratio, external aid and per capita income impact significantly and positively on current level of development in human capital, while, government social expenditure, inflation, current value of student – teacher ratio and lagged value of external aid show a negative relationship with human capital development. In view of the above findings, the study recommends that social expenditure should be given more serious attention, while adequate measure should be taken to ensure that economic expenditure yield its preferred results. The study concludes that resources should be properly channeled (and monitored) to areas of expenditure that would boost human capital development in Nigeria.